Occurrence and distribution of perfluoroalkyl substances in surface riverine and coastal sediments from the Beibu Gulf, south China. (January 2020) - Pan, Chang-Gui; Wang, Ying-Hui; Yu, Ke-Fu; Zhang, Wei; Zhang, Jun; Guo, Jing
Abstract: There is limited understanding on the occurrence of PFASs in coastal sediment, especially in less-developed coastal areas. Here, we collected surface sediment samples from the Beibu Gulf to investigate the occurrence, spatial distribution and environmental risks of 18 PFASs. The concentrations of the total PFASs (ΣPFASs) ranged from 56.2 to 586.3 pg/g dry weight (dw), with a mean value of 172.5 pg/g dw. ΣPFASs concentrations were significantly lower in riverine than in coastal sediments. Additionally, there was a decreasing trend in ΣPFASs concentrations from the west (Fangchenggang) to the east (Beihai) of the Beibu Gulf. Perfluorooctanoic acid (PFOA) and perfluorooctane sulfonate (PFOS) were the predominant PFASs, with their concentrations in the range of 4.8–249.0 pg/g dw and not detected (n.d)-224.8 pg/g dw, respectively. On a global scale, PFOS and PFOA concentrations were at low levels in the sediment of the Beibu Gulf, and they posed negligible environmental risks. Graphical abstract: Image 1 Highlights: A comprehensive survey of PFASs in the sediment of Beibu Gulf was performed. ΣPFASs concentrations ranged from 56.2 to 586.3 pg/g dw in the Beibu Gulf. PFOA and PFOS were the dominant PFASs in the sediment. ΣPFASs levels in coastal sediments were significantly higher than in riverine sediments. The environmental risk of PFOA and PFOS were negligible in the Beibu Gulf.